PATIENCE AND PSYCHOLOGICAL WELFARE ON STUDENTS WORKING PART-TIME DURING COVID-19 IN BANDA ACEH - Safrilsyah, Safrilsyah; Fitri, Putri Rahma; Karjuniwati, Karjuniwati (Psikoislamedia: Jurnal Psikologi, 2023)
Psychological well-being is one of the most important things in human life, especially for students working part-time during COVID-19. One of the factors that can affect psychological well-being is patience. The purpose of this study was to determine the relationship between patience and psychological well-being in UIN Ar-Raniry students working part-time during COVID-19. This study uses a correlational quantitative approach. The measuring tools in this study are the patience scale from Subandi (2011) and the psychological well-being scale from Ryff and Singer (2008). . The sample in this study were 211 people. Sampling using non-probability sampling method with accidental sampling technique. The results of this study show a correlation coefficient of r = 0.839 with p = 0.000 (p < 0.05) which indicates that there is a very significant positive relationship between patience and psychological well-being in UIN Ar-Raniry students working part-time during covid-19. This means that the higher the patience, the higher the psychological well-being felt by students and the lower the patience, the lower the psychological well-being felt by the students.